Evolutionary conservation and functional roles of ncRNA - Qu, Zhipeng; Adelson, David L. (Frontiers in Genetics, 2012)
Non-coding RNAs (ncRNAs) are a class of transcribed RNA molecules without protein-coding potential. They were regarded as transcriptional noise, or the byproduct of genetic information flow from DNA to protein for a long time. However, in recent years, a number of studies have shown that ncRNAs are pervasively transcribed, and most of them show evidence of evolutionary conservation, although less conserved than protein-coding genes. More importantly, many ncRNAs have been confirmed as playing crucial regulatory roles in diverse biological processes and tumorigenesis. Here we summarize the functional significance of this class of “dark matter” in terms its genomic organization, evolutionary conservation and broad functional classes.